La transmission universitaire des textes médiévaux : pleine propriété ou usufruit d’un héritage ? Imaginaires critiques du proche et du lointain - Sarah Delale (Perspectives Médiévales)
The end of the 20th century was the time of a proliferation in new media (video games, TV series…) of “mediaevalist” productions, whose relation to the Middle Ages is of a stylistic, rather than a historical, nature. The same period also witnessed the appearance in academia of methods for textual analysis competing with literary history. These new methods waived the ban on anachronism that had so far been the cornerstone of mediaeval studies. This contribution offers an overview of these methods (from literary history to the theory of the possible texts) and of their relation to the mediaeval text’s age. An aged text presents the reader with a choice between otherness and familiarity, between closeness and remoteness, and therefore between sets of interpretational limits that vary according to the chosen method. Whereas mediaevalist works have altered the students’ conception of the Middle Ages, the mode of their inheritance of mediaeval texts remains to be defined. Is it an usufruct founded on a notion of historical truth, or a full ownership allowing either new or self-seeking interpretations?